Method for preparing Na2FePO4F-coated TiO2 heterostructure material through atomic layer deposition technology
By combining atomic layer deposition technology and annealing technology, Na2FePO4F@TiO2 heterostructured material was prepared, which solved the problem of insufficient mechanical properties and cycle stability of Na2FePO4F material, achieved higher mechanical properties and cycle stability, and improved the overall performance of sodium ion batteries.
Patent Information
- Application Number
- CN202411925391.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing sodium ion battery positive electrode material Na2FePO4F has poor mechanical properties and cycle stability, and traditional modification methods are difficult to achieve a uniform and dense coating, which affects battery performance.
By combining atomic layer deposition technology and annealing technology, Na2FePO4F@TiO2 heterostructure material is prepared to achieve Ti substitution and anchoring of trace Ti, and enhance the mechanical properties and cyclic stability of the material.
It improves the mechanical properties and cycle stability of Na2FePO4F material, reduces the direct contact between the material and the electrolyte, inhibits the occurrence of side reactions, and improves the overall performance of the battery.
Smart Images

Figure CN119725464A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery positive electrode materials and relates to a Na 2 FePO 4 F@TiO 2 A method for preparing heterogeneous structure materials, specifically a method for preparing Na by atomic layer deposition technology 2 FePO 4 F@TiO 2 Methods for heterostructured materials. Background Art
[0002] As an emerging rechargeable battery, sodium-ion batteries have broad development prospects due to their rich raw material resources, excellent safety performance, and production lines that can draw on existing lithium-ion batteries. 2 FePO 4 As a kind of phosphate polyanion material, F has a simple synthesis process. Due to the stronger induction effect of fluoride ions, it effectively improves the redox couple and has a higher working voltage and discharge specific capacity, but the specific capacity retention rate is slightly worse. The traditional modification method is mainly to increase the Na 2 FePO 4 The intrinsic conductivity of F material. This method has low controllability over the thickness of the coating layer, making it difficult to achieve uniform and dense coverage of carbon. In addition, the bonding between the coating layer and the material is poor, and it may fall off during subsequent processing such as mixing with paste and coating, seriously affecting the performance of the battery. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present invention provides a method for preparing Na 2 FePO 4 F@TiO 2 This method combines atomic layer deposition technology with annealing technology to construct a phase interface Na with freely adjustable physical and chemical properties by changing the number of deposition cycles and annealing temperature. 2 FePO 4 F@TiO 2 Heterostructure, realizing Na 2 FePO 4 The Ti substitution of F, the special heterostructure and the anchoring effect of trace Ti enhance the mechanical properties and cycle stability of the material.
[0004] The objective of the present invention is achieved through the following technical solutions:
[0005] A method for preparing Na by atomic layer deposition 2 FePO 4 F@TiO 2The method of heterogeneous structure material comprises the following steps:
[0006] Step 1: Preparation of sodium fluoroferric phosphate:
[0007] Step 11, ball milling: mix and ball mill the phosphorus source, fluorine source, iron source and sodium source according to the molar ratio of 1.0-1.5:1.0-1.3:1.0-1.5:2.0-2.5, wherein:
[0008] The phosphorus source is one or more of ferric phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, ammonium monohydrogen phosphate, sodium monohydrogen phosphate, phosphoric acid, sodium hypophosphite, sodium phosphite, ferric hypophosphite, ferric phosphite, ammonium hypophosphite, sodium phosphate ester compounds, and ammonium phosphate ester compounds;
[0009] The fluorine source is one or more of sodium fluoride, ferric fluoride, tetrafluoroethylene, vinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride, fluorobenzene, fluoroacetic acid, and perfluoroalkyl carboxylic acid;
[0010] The iron source is one or more of iron powder, iron oxide, ferrous oxalate, ferrous acetate, ferric hydroxide, ferrous hydroxide, ferrous lactate, ferrous citrate, and ferrocene;
[0011] The sodium source is one or more of sodium bicarbonate, sodium carbonate, sodium hydroxide, sodium citrate, sodium gluconate, sodium acetate, sodium phenolate, sodium ethoxide, and sodium acetylide;
[0012] The ball milling time is 18 to 24 hours, and the ball milling medium is one of deionized water and anhydrous ethanol;
[0013] Step 1 and 2, sintering: After vacuum drying the product obtained by ball milling, sintering in a tubular furnace under an inert atmosphere, and cooling to obtain a sodium iron fluoride phosphate material, wherein:
[0014] The vacuum drying time is 20 to 30 hours;
[0015] The inert atmosphere is one or more of argon, hydrogen, nitrogen and helium;
[0016] The sintering temperature is 600-800°C and the sintering time is 10-14h;
[0017] Step 2: Atomic layer deposition technology to deposit TiO 2 film:
[0018] Step 21: Deposition of TiO 2 Thin film: Using ALD atomic deposition technology, titanium source and oxygen source are selected as precursors, inert gas is introduced, and redox reaction occurs on the surface of sodium iron fluoride phosphate material to deposit dense TiO 2 Thin films, wherein:
[0019] The titanium source is one or more of titanium tetrachloride, titanium tetraiodide, titanium tetraisopropoxide, tetramethyl titanium, titanium tetraethoxide, titanium tetrabutoxide, and titanium pentacarbonyl;
[0020] The oxygen source is H 2 O, O 2 , O 3 One or more of the following;
[0021] The inert gas is one or more of argon, hydrogen, nitrogen and helium, the flow rate of the inert gas is 50-100 ml / min, and the duration is 60-120 s;
[0022] Step 2. Cycle: By changing the number of atomic deposition cycles, the TiO deposited on the surface of the sodium iron fluoride phosphate material can be controlled. 2 The thickness and physical and chemical properties of the film, including:
[0023] The number of cycles of the atomic deposition is 4 to 10 times;
[0024] Step 3: Annealing:
[0025] TiO was deposited on the surface 2 The sodium fluorinated phosphate film was annealed and TiO was deposited on part of the surface. 2 The Ti in the NaFPO4 enters the lattice and replaces Fe ions, forming a partially Ti-doped Na 2 FePO 4 F@TiO 2 Heterogeneous structural materials, where:
[0026] The annealing temperature is 300-600° C.
[0027] The Na 2 FePO 4 F@TiO 2 Heterostructure materials can be used in positive electrode materials of sodium ion batteries.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] The present invention combines atomic layer deposition technology with annealing technology to prepare Ti-substituted Na with controllable physical and chemical properties by adjusting the number of atomic deposition cycles and annealing temperature. 2 FePO 4 F@TiO 2 Heterogeneous structural materials form a TiO layer with adjustable thickness and tight bonding on the outer layer of the material. 2The micro-scale heterogeneous structure formed by annealing effectively enhances the mechanical properties of the material and reduces the direct contact between the material and the electrolyte, thereby inhibiting the occurrence of possible side reactions. At the same time, the trace Ti substitution achieved in one step plays an anchoring role without changing the original crystal structure, effectively preventing structural deformation and reducing internal stress changes, effectively improving Na 2 FePO 4 Mechanical properties and cyclic stability of F materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Deposition of TiO by atomic layer deposition technology of the present invention 2 Schematic diagram of the film process;
[0031] Figure 2 The Na prepared in Example 2 2 FePO 4 F@TiO 2 Schematic diagram of the structure of heterostructure materials;
[0032] Figure 3 The Na prepared in Example 2 2 FePO 4 F@TiO 2 SEM images of heterostructured materials;
[0033] Figure 4 The Na prepared in Example 2 2 FePO 4 F@TiO 2 Charge and discharge curves of heterostructure materials;
[0034] Figure 5 The Na prepared in Example 2 2 FePO 4 F@TiO 2 Heterostructured materials and unmodified Na 2 FePO 4 Comparison chart of the cycling performance of F materials. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0036] Embodiment 1:
[0037] This embodiment provides a method for preparing Na 2 FePO 4 F@TiO2 A method for heterogeneous structural materials, the method comprising the following steps:
[0038] Step 1: Preparation of sodium fluoroferric phosphate:
[0039] Step 11, ball milling: ferric phosphate, sodium fluoride, ferrous oxalate, and sodium bicarbonate are mixed at a molar ratio of 1.0:1.0:1.0:2.1 and ball milled for 18 hours, and the solvent is deionized water;
[0040] Step 1 and 2, sintering: vacuum drying the ball milled product for 24 hours, sintering it at 600° C. for 14 hours in an inert atmosphere in a tubular furnace, and cooling it to obtain the sodium iron phosphate fluoride material, wherein the inert atmosphere is hydrogen and argon;
[0041] Step 2: Atomic layer deposition technology to deposit TiO 2 film:
[0042] Step 21: Deposition of TiO 2 Thin film: ALD atomic deposition technology is used, titanium tetrachloride, H 2 O was used as a precursor, and an inert gas was introduced at a flow rate of 100 ml / min for 60 s to cause a redox reaction on the surface of the sodium iron fluoride phosphate material to deposit a dense TiO 2 Film, the inert gas is hydrogen and argon;
[0043] Step 2. Cycle: By changing the number of atomic deposition cycles, the TiO deposited on the surface of the sodium iron fluoride phosphate material can be controlled. 2 The thickness and physical and chemical properties of the film, wherein: the number of cycles of the atomic deposition is 4;
[0044] Step 3: Annealing:
[0045] TiO was deposited on the surface 2 The sodium iron phosphate fluoride material of the film was annealed at 480 °C, and TiO was deposited on part of the surface. 2 The Ti in the NaFPO4 enters the lattice and replaces Fe ions, forming a partially Ti-doped Na 2 FePO 4 F@TiO 2 Heterogeneous structural materials.
[0046] Embodiment 2:
[0047] This embodiment provides a method for preparing Na 2 FePO 4 F@TiO 2 A method for heterogeneous structural materials, the method comprising the following steps:
[0048] Step 1: Preparation of sodium fluoroferric phosphate:
[0049] Step 11, ball milling: ammonium dihydrogen phosphate, sodium fluoride, ferrous acetate, and sodium hydroxide are mixed at a molar ratio of 1.1:1.0:1.2:2.2 and ball milled for 20 hours, and the solvent is deionized water;
[0050] Step 1 and 2, sintering: vacuum drying the ball milled product for 24 hours, sintering it in a tube furnace at 700° C. for 17 hours in an inert atmosphere, and cooling it to obtain the sodium iron phosphate fluoride material, wherein the inert atmosphere is argon;
[0051] Step 2: Atomic layer deposition technology to deposit TiO 2 film:
[0052] Step 21: Deposition of TiO 2 Thin film: ALD atomic deposition technology is used, titanium tetrachloride, H 2 O and O 2 As a precursor, an inert gas was introduced at 80 ml / min for 100 s to cause a redox reaction on the surface of the sodium iron fluoride phosphate material to deposit a dense TiO 2 film, wherein the inert gas is argon;
[0053] Step 2. Cycle: By changing the number of atomic deposition cycles, the TiO deposited on the surface of the sodium iron fluoride phosphate material can be controlled. 2 The thickness and physical and chemical properties of the film, wherein: the number of cycles of the atomic deposition is 5 times;
[0054] Step 3: Annealing:
[0055] TiO was deposited on the surface 2 The sodium iron phosphate fluoride material of the film was annealed at 550 °C, and TiO was deposited on part of the surface. 2 The Ti in the NaFPO4 enters the lattice and replaces Fe ions, forming a partially Ti-doped Na 2 FePO 4 F@TiO 2 Heterogeneous structural materials, the structural diagram of which is shown in Figure 2 shown.
[0056] Embodiment 3:
[0057] This embodiment provides a method for preparing Na 2 FePO 4 F@TiO 2 A method for heterogeneous structural materials, the method comprising the following steps:
[0058] Step 1: Preparation of sodium fluoroferric phosphate:
[0059] Step 11, ball milling: Sodium dihydrogen phosphate, ferric fluoride, ferric hydroxide, and sodium carbonate are mixed at a molar ratio of 1.1:1.1:1.1:2.1 and ball milled for 24 hours, and the solvent is anhydrous ethanol;
[0060] Step 1 and 2, sintering: vacuum drying the ball milled product for 24 hours, sintering it in a tube furnace at 800° C. for 10 hours in an inert atmosphere, and cooling it to obtain the sodium iron phosphate fluoride material, wherein the inert atmosphere is a mixed gas of argon and nitrogen;
[0061] Step 2: Atomic layer deposition technology to deposit TiO 2 film:
[0062] 3) Deposition of TiO 2 Thin film: Using ALD atomic deposition technology, titanium source and oxygen source are selected as precursors, and an inert gas is introduced at a certain flow rate for a certain period of time to cause a redox reaction on the surface of the sodium iron fluoride phosphate material to deposit dense TiO 2 film;
[0063] 4) Cycle: By changing the number of atomic deposition cycles, the TiO deposited on the surface of the sodium iron fluoride phosphate material can be regulated. 2 The thickness and physical and chemical properties of the film;
[0064] Step 21: Deposition of TiO 2 Thin film: ALD atomic deposition technology is used to select titanium tetraisopropoxide and O 3 As a precursor, an inert gas was introduced at 60 ml / min for 120 s to cause a redox reaction on the surface of the sodium iron fluoride phosphate material to deposit a dense TiO 2 The film, the inert gas is a mixed gas of argon and nitrogen;
[0065] Step 2. Cycle: By changing the number of atomic deposition cycles, the TiO deposited on the surface of the sodium iron fluoride phosphate material can be controlled. 2 The thickness and physical and chemical properties of the film, wherein: the number of cycles of the atomic deposition is 8 times;
[0066] Step 3: Annealing:
[0067] TiO was deposited on the surface 2 The sodium iron phosphate fluoride material of the film was annealed at 600°C, and TiO was deposited on part of the surface. 2 The Ti in the NaFPO4 enters the lattice and replaces Fe ions, forming a partially Ti-doped Na 2 FePO 4 F@TiO 2 Heterogeneous structural materials.
[0068] Test and analyze product morphology and battery cycle performance:
[0069] (1)Na 2 FePO 4 F@TiO 2 SEM images of heterostructured materials
[0070] Scanning electron microscopy (SEM) is a basic analytical technique for exploring the microstructure of materials. The present invention uses the GEMINI 500 SEM equipment of the German ZEISS company to characterize the surface morphology of the sample. In order to ensure a clearer display of the material morphology, the material needs to be pre-treated by gold spraying to enhance the material's electrical conductivity. Figure 3 The Na prepared in Example 2 2 FePO 4 F@TiO 2 SEM images of heterogeneous structure materials, from Figure 3 It can be seen that the Na prepared in Example 2 2 FePO 4 F@TiO 2 The heterostructured material consists of a series of particles with diameters ranging from 6 to 8 μm.
[0071] (2)Na 2 FePO 4 F@TiO 2 Electrochemical performance testing of heterostructured materials
[0072] In order to evaluate the electrochemical properties of the prepared materials, half-cells were designed and assembled for testing. First, 200 mg of the material prepared in Example 2 and 25 mg of the conductive additive were weighed and ground in a mortar for 20 min to ensure uniform mixing. The mixed powder was transferred to a paste bottle, 500 mg of a pre-made NMP solution containing 5 wt% PVDF was added thereto, and an appropriate amount of NMP was supplemented to adjust the viscosity. A uniform paste was formed after magnetic stirring for about 18 hours. Subsequently, a 120 μm scraper was used to evenly coat the paste on aluminum foil, and after drying at 120 ° C under vacuum for 12 hours, it was cut into positive electrode sheets with a diameter of 12 mm. Finally, the electrode sheet, glass fiber diaphragm, and sodium sheet were assembled into a CR2032 button battery in an inert argon atmosphere glove box, and the electrolyte was 1.0 M NaClO 4 / EC-PC (volume ratio 1:1, 5.0Vol% FEC). The button cell is charged and discharged at a constant current of 0.2C (1C = 120mAh / g) in the voltage range of 2.0 to 4.0V. The charge and discharge curve is shown in the figure below. Figure 4 As shown, compared with the unmodified Na 2 FePO 4 The comparison of the cycling performance of F materials is shown in the figure Figure 5 The charge and discharge test results are shown in Table 1.
[0073] Table 1 Charge and discharge test results
[0074]
[0075] It can be seen from Table 1 that within a certain range of conditions, changing the raw material ratio, the number of atomic deposition cycles, the annealing temperature and other conditions will have an impact on the obtained Na 2 FePO 4 F@TiO 2 The electrochemical properties of heterostructured materials are slightly affected, but the overall performance consistency is still high. Figure 4 , 5 It can be seen that the prepared Na 2 FePO 4 F@TiO 2 The heterostructured material has a smooth charge-discharge curve, and the discharge platform area is relatively concentrated, which is better than the unmodified Na 2 FePO 4 F material has obvious improvements in discharge specific capacity and cycle stability, and has good application prospects.
Claims
1. A method for preparing Na2FePO4F@TiO2 heterostructure material by atomic layer deposition technology, characterized in that The method comprises the following steps: Step 1: Preparation of sodium fluoroferric phosphate: Step 11, ball milling: mixing and ball milling the phosphorus source, fluorine source, iron source and sodium source according to the molar ratio of 1.0-1.5:1.0-1.3:1.0-1.5:2.0-2.5; Step 1 and 2, sintering: vacuum drying the ball milled product, sintering it in a tubular furnace under an inert atmosphere, and cooling it to obtain the sodium iron fluoride phosphate material; Step 2: Deposit TiO2 thin film using atomic layer deposition technology: Step 21. Depositing TiO2 thin film: Using ALD atomic deposition technology, titanium source and oxygen source are selected as precursors, inert gas is introduced, and redox reaction occurs on the surface of sodium iron fluoride phosphate material to deposit a dense TiO2 thin film; Step 22: Cycle: By changing the number of atomic deposition cycles, the thickness and physical and chemical properties of the TiO2 film deposited on the surface of the sodium iron fluoride phosphate material can be controlled; Step 3: Annealing: The sodium iron phosphate fluoride material with TiO2 film deposited on the surface is annealed, and Ti in part of the surface deposited TiO2 enters the sodium iron phosphate fluoride lattice and replaces Fe ions, forming a partially Ti-doped Na2FePO4F@TiO2 heterostructure material.
2. The method for preparing Na2FePO4F@TiO2 heterostructure material by atomic layer deposition technology according to claim 1, characterized in that The phosphorus source is one or more of ferric phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, ammonium monohydrogen phosphate, sodium monohydrogen phosphate, phosphoric acid, sodium hypophosphite, sodium phosphite, ferric hypophosphite, ferric phosphite, ammonium hypophosphite, sodium phosphate compounds, and ammonium phosphate compounds; the fluorine source is one or more of sodium fluoride, ferric fluoride, tetrafluoroethylene, vinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride, fluorobenzene, fluoroacetic acid, and perfluoroalkyl carboxylic acid; the iron source is one or more of iron powder, iron oxide, ferrous oxalate, ferrous acetate, ferric hydroxide, ferrous hydroxide, ferrous lactate, ferric citrate, and ferrocene; the sodium source is one or more of sodium bicarbonate, sodium carbonate, sodium hydroxide, sodium citrate, sodium gluconate, sodium acetate, sodium phenolate, sodium ethoxide, and sodium acetylide.
3. The method for preparing Na2FePO4F@TiO2 heterostructure material by atomic layer deposition technology according to claim 1, characterized in that The ball milling time is 18 to 24 hours, and the ball milling medium is one of deionized water and anhydrous ethanol.
4. The method for preparing Na2FePO4F@TiO2 heterostructure material by atomic layer deposition technology according to claim 1, characterized in that The vacuum drying time is 20 to 30 hours; the inert atmosphere is one or more of argon, hydrogen, nitrogen and helium; the sintering temperature is 600 to 800° C. and the time is 10 to 14 hours.
5. The method for preparing Na2FePO4F@TiO2 heterostructure material by atomic layer deposition technology according to claim 1, characterized in that The titanium source is one or more of titanium tetrachloride, titanium tetraiodide, titanium tetraisopropoxide, tetramethyl titanium, tetraethoxy titanium, titanium tetrabutoxide, and titanium pentacarbonyl; the oxygen source is one or more of H2O, O2, and O3.
6. The method for preparing Na2FePO4F@TiO2 heterostructure material by atomic layer deposition technology according to claim 1, characterized in that The inert gas is one or more of argon, hydrogen, nitrogen and helium. The flow rate of the inert gas is 50-100 ml / min and the duration is 60-120 s.
7. The method for preparing Na2FePO4F@TiO2 heterostructure material by atomic layer deposition technology according to claim 1, characterized in that The number of cycles of the atomic deposition is 4 to 10 times.
8. The method for preparing Na2FePO4F@TiO2 heterostructure material by atomic layer deposition technology according to claim 1, characterized in that The annealing temperature is 300-600°C.
9. A Na2FePO4F@TiO2 heterostructure material prepared by the method according to any one of claims 1 to 8.
10. Use of the Na2FePO4F@TiO2 heterostructure material prepared by the method according to any one of claims 1 to 8 in a positive electrode material for a sodium ion battery.
Citation Information
Patent Citations
Sedimentary sodium iron phosphate positive electrode material and preparation method and application thereof
CN114068906A
Carbon-coated sodium ferrous fluorophosphate positive electrode active material, preparation thereof and application of carbon-coated sodium ferrous fluorophosphate positive electrode active material in sodium ion battery
CN114122311A
Positive electrode material of metallic oxide coated sodium ferric fluorophosphate as well as preparation method and application of positive electrode material
CN117577805A
Atomic layer deposition modified sodium ion battery positive electrode material and preparation method and application thereof
CN117855420A
Deposited sodium iron phosphate positive electrode material, and preparation method therefor and application thereof
WO2023060989A1